MAKNA SOSIAL-RELIGIUS SEBAGAI NILAI KONSELING ISLAM DALAM TRADISI KETOG SEMPRONGDI KABUPATEN TABANAN BALI - Juwairiyah; Hanik Mufaridah (Fakultas Dakwah Universitas Ibrahimy, 2024)
Humans as social creatures must always maintain good relationships with others because it is an obligation that must be carried out. Just as tradition can create a society that has a social spirit, so that social relations can create harmony in people's lives. From observing the conditions above, researchers examined various facts regarding the socio - religious meaning of Islamic counseling values in the Ketog Semprong tradition in Tabanan Regency, Bali. The aim of this research is to describe the procession of the Ketog Semprong tradition and to describe the socio - religious meaning of Islamic counseling values in the Ketog Semprong tradition in Tabanan Regency, Bali. In the re search method to obtain comprehensive information and data, this research uses a qualitative research approach with the type of ethnographic qualitative research. The results of the research show that: First, the Ketog Semprong traditional procession in Ta banan district, Bali, has three processions, namely joint prayer, megibung sagi or eating together, and art performances. And secondly, the social - religious meaning as an Islamic counseling value in the Ketog Semprong tradition in Tabanan district, Bali. T here are two Islamic counseling values that exist in this tradition, namely the first, spiritual values such as praying together, and the second, your values. 'Amalah or social such as an attitude of mutual sharing, an attitude of affection, an attitud e of mutual cooperation in the form of mutual assistance, an attitude of tolerance in religion so that it can foster harmony, and finally an attitude of togetherness. All these attitudes can foster harmony and happiness which can be used as provisions for social life.